Alternative Treatment for Iatrogenic Dermatoporosis - Cassain, Fernanda; Gonzaga, Marisa; Soares, Jeovana; Viana, Renata; Serra, Márcio (Brazilian Journal of Case Reports, 2024)
A healthy 60-year-old female patient, with a history of Quervain’s Syndrome, presented with corticosteroid-induced dermatoporosis after receiving intra-articular corticosteroid injections. She experienced skin fragility and aesthetic discomfort due to dermal atrophy and a violaceous macule at the injection site. Treatment with calcium hydroxyapatite (CaHA) biostimulator was initiated, resulting in significant improvements in skin quality and pigmentation. Following two sessions, the patient reported enhanced self-esteem and satisfaction with the treatment outcomes. This case underscores the potential of CaHA as an effective therapeutic option for managing early stages of dermatoporosis.